PENGARUH MARKETING MIX TERHADAP KEPUTUSAN KONSUMEN UNTUK MENABUNG PADA BANK PERKREDITAN RAKYAT - Dewi Ayu Mayangsari Tiwow; Celcius Talumingan; Charles R. Ngangi; Tommy F. Lolowang (Universitas Sam Ratulangi, 2013)
AbstrakThe objective of this research is to determine the effect of marketing mix (Product,Promotion, Place, Price, Process, People and Physical Evidence) to the decision of consumerswho save money on PT. BPR Dana Raya Manado and to see which variable is dominant tothe decisions of consumers who save. The research was conducted at PT. BPR Dana RayaManado. Data is processed by using the method of multiple regression analysis, with SPSS 20statistical calculations. This research used primary and secondary data. The first primary datawas obtained from interviews with respondents by on a list of questions (questionnaires).While the secondary data obtained from the relevant authorities in this study. The method ofdata analysis is to test the validity and reliability testing and multiple regression analysiswith F test and t test.The results of the research showed that 70,3% of independent variables(X1, X2, X3, X4, X5, X6 and X7) jointly have an influence on the dependent variable (Y),while the remaining 29,7% of consumer decisions is explained by other causes in outsideresearch. The results of the F test analysis showed that the F calculated > F-table with avalue of 17,578 > 2,2371 which means that the variable X (product, promotion, place, price,process, people and physical evidence) significantly influence consumer decisions. Through thet test analysis, each variable X has the value t-count > t-table, where the dominant promotionvariable (X2) that is equal to 0,291 (29,1%).